Перфекціонізм у сучасному житті: психологічні механізми та практичні імплікації - Гуляс, Інеса; Онуфрієва, Ліана (My University, 2026)
The aim of the article. The article is aimed at conceptually understanding perfectionism as a complex and structurally organized psychological construct, outlining its content dimensions, determinants of its formation and features of manifestation in modern sociocultural conditions, as well as determining applied guidelines for the practice of psychological counseling and psychoprophylactic work. Methods. A set of theoretical methods was used: theoretical analysis and synthesis to generalize scientific approaches to the interpretation of perfectionism; comparative analysis to compare unidimensional and multidimensional models; systematization and generalization of scientific sources to structure data on the impact of perfectionistic attitudes on psychological wellbeing; logi-calstructural analysis to determine applied vectors of psychological assistance. The results of the research. The results of the study showed the departure of modern psychology from the unitary interpretation of perfectionism as an ex-clusively maladaptive trait and the affirmation of its ambivalent understanding. The feasibility of distinguishing adaptive perfectionist aspirations and maladap-tive perfectionist concerns is substantiated. It is shown that the former can per-form a resource function and correlate with personal growth and achievements, while the latter are predictors of anxiety, depressive symptoms, emotional burn-out and decreased psychological wellbeing. Modern approaches to psychologi-cal assistance focused on the transformation of maladaptive cognitiveemotional patterns and the preservation of the motivational potential of high standards are summarized.Conclusion. Perfectionism should be considered as a structurally differentiated and contextually determined phenomenon, the impact of which on psy-chological functioning is determined by the ratio of its components. Effective psy-chological support strategies should be based on an individualized assessment of adaptive and maladaptive aspects of perfectionism and their targeted correction.
Keywords: perfectionism, multidimensionality of perfectionism, adaptive perfectionism, maladaptive perfectionism, perfectionistic aspirations, perfec tionistic concerns, psychological wellbeing, psychological distress, emotional burnout, psychological counseling